Discussion of “Attitude of Physi -cians Towards Automatic Alerting in Computerized Physician Order Entry Systems” - Bates, D. W.; Baysari, M. T.; Dugas, M.; Haefeli, W. E.; Kushniruk, A. W.; Lehmann, C. U.; Liu, J.; Mantas, J.; Margolis, A.; Miyo, K.; Nohr, C.; Peleg, M.; de Quirós, F. G. B.; Slight, S. P.; Starmer, J.; Takabayashi, K.; Westbrook, J. I. (Methods of Information in Medicine, 2013)
With these comments on the paper “Attitude of Physicians Towards Automatic Alerting in Computerized Physician Order Entry Systems”, written by Martin Jung and co authors, with Dr. Elske Ammenwerth as senior author [1], the journal wants to stimulate a broad discussion on computerized physi cian order entry systems. An international group of experts have been invited by the editor of Methods to comment on this paper. Each of the invited commentaries forms one section of this paper.
Keywords: Medical order entry systems; clinical decision support systems; attitude; questionnaires; alerting